The conspiracy club - Kellerman, Jonathan (Random House Audio, 2003)
Devastated and suspected by the police after the brutal murder of his girlfriend, psychologist Jeremy Carrier finds himself engaged in a game of cat and mouse when additional murders take place and clues begin appearing in his mail.